The Effect of Company Size, Profitability and Company Age on the Timeless of Financial Reporting - Asiah, Neng; Sapruwan, Muhammad; Irwanti, Lia Ayu (International Journal of Asian Business and Management, 2024)
This research seeks to evaluate how financial reporting timeliness is influenced by  three key variable—company size, profitability, and company age. Timely financial reporting holds significance in the realm of corporate finance, as it enables stakeholders to make more informed decisions. The study focuses on companies listed on the stock exchange that have released financial reports in recent years, specifically examining properties and real estate firms listed on the Indonesia Stock Exchange between 2019 and 2021. To examine the correlation between the independent variables (company size, profitability, and company age) and the dependent variable (timeliness of financial reporting), the study employs various statistical analyses, including linear regression. The research follows a quantitative descriptive approach, involving descriptive statistical data analysis, classical assumption testing, multiple linear regression tests, hypothesis testing, and coefficient of determination test. The result indicate that all independent variables have a simultaneous effect on the timeliness of financial reporting. Partially the variables of company size company size and profitability have a negative effect, whereas the age of the company has no effect on the timeliness of financial statements. This suggests that fundamental factors associated with a company play a crucial role in determining the accuracy of its financial reports